Hubungan Supervisi Akademik Dan Kepemimpinan Transformasional Kepala Sekolah Penggerak Dengan Profesionalisme Guru Di Korwil Periuk - Karsono Karsono; Cecep Anwar Hadi Firdos Santosa; Sri Tatminingsih; Yus Alvar Saabighoot (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
Study and analysis of the relationship between academic supervision and the leadership of driving school principals and teacher professionalism in Korwil Periuk is the aim of the research. The sample used 98 teachers. Research type is quantitative using survey methods. Analysis method is descriptive analysis, analysis prerequisite tests, coefficient of determination analysis and hypothesis testing. Hypothesis testing uses a partial test with the product moment correlation  and a simultaneous test uses the F test formula. Conclusions results: (1) there is a positive relationship between the principal's academic supervision and the professionalism of teachers in Korwil Periuk. (2) there is a positive relationship between the transformational leadership of driving school principals and the professionalism of teachers at Korwil Periuk. (3) there is a positive relationship simultaneously between the academic supervision and transformational leadership of the principal of the Driving School and the professionalism of teachers in Korwil Periuk.